2019
DOI: 10.1111/acfi.12541
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, social, and governance practices and perceived tail risk

Abstract: Using the implied volatility smirk on individual equity securities to measure perceived tail risk, we find that better environmental, social and governance (ESG) practices significantly reduce ex‐ante expectations of a left‐tail event. Our findings are robust to using multiple model specifications and to adjusting for potential endogeneity concerns. We also show that, while practices in each ESG pillar are important in reducing perceived tail risk, the environmental pillar plays the most important role. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Until now, most scholars have focused on the link between ESG scores and corporate financial performance (e.g., Friede et al (2015); Cornett et al (2016); Henke (2016); El Ghoul et al (2017); Hou et al (2019); Behl et al (2021); Kalaitzoglou et al (2021)). Then recently, some studies have started to analyze the link between ESG scores and risk measures (e.g., Shafer et al (2020); Bax et al (2021); Giese et al (2021); Maiti (2021)). Additionally, ESG data quality issues and the impact of ESG‐type corporate disclosures on investment allocations have been another center of attention in the ESG literature and which is where our work contributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Until now, most scholars have focused on the link between ESG scores and corporate financial performance (e.g., Friede et al (2015); Cornett et al (2016); Henke (2016); El Ghoul et al (2017); Hou et al (2019); Behl et al (2021); Kalaitzoglou et al (2021)). Then recently, some studies have started to analyze the link between ESG scores and risk measures (e.g., Shafer et al (2020); Bax et al (2021); Giese et al (2021); Maiti (2021)). Additionally, ESG data quality issues and the impact of ESG‐type corporate disclosures on investment allocations have been another center of attention in the ESG literature and which is where our work contributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This could lead to potential valuation risk which should be considered before any investment decision (Dunn et al, 2018;Lioui, 2018;Pollard et al, 2018;Berg and Lange, 2020). Some researchers argue that responsible ESG practices might mitigate the market's perception of a company's tail risk and, therefore, reduce ex-ante expectations of a left-tail event (Shafer and Szado, 2018). In brief, they state that considering responsible business practices when creating an equity portfolio can act as insurance against left-tail risk and, with that, protect company value.…”
Section: Esg Scores Dependence and Riskmentioning
confidence: 99%
“…Ashwin Kumar et al (2016) add that positive ESG practices can make a company less vulnerable to reputation, political and regulatory risk and thus leading to lower volatility of cash flows and profitability' (p. 292). Furthermore, positive ESG performance may generate more loyalty from customers and employees plus, through that, protect companies from unforeseen harmful events, resulting in reduced tail risk (Shafer and Szado, 2018). Besides, better ESG performance allows companies to experience adverse events less often and loose less value if they do occur (Minor, 2011).…”
Section: Esg Scores Dependence and Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bax et al (2021) have shown, using vine copula models, that ESG scores exhibit around 30% a (tail) dependence relationship with the Value-at-Risk (VaR) risk measure. Other scholars find that better ESG ratings can be linked to lower downside risk and also reduce perceived tail risk (e.g., Shafer & Szado (2020); Giese et al (2021); Lööf et al (2021)). ESG ratings, therefore, could carry information on risk and help investors to distinguish stocks with high-risk exposure (Lööf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%